Transcriptome evidence reveals enhanced autophagy-lysosomal function in centenarians - Xiao, Fu-Hui; Chen, Xiao-Qiong; Yu, Qin; Ye, Yunshuang; Liu, Yao-Wen; Yan, Dongjing; Yang, Li-Qin; Chen, Guijun; Lin, Rong; Yang, Liping; Liao, Xiaoping; Zhang, Wen; et al. (Genome research, 2018)
Centenarians (CENs) are excellent subjects to study the mechanisms of human longevity and healthy aging. Here, we analyzed the transcriptomes of 76 centenarians, 54 centenarian-children, and 41 spouses of centenarian-children by RNA sequencing and found that, among the significantly differentially expressed genes (SDEGs) exhibited by CENs, the autophagy-lysosomal pathway is significantly up-regulated. Overexpression of several genes from this pathway, CTSB , ATP6V0C , ATG4D , and WIPI1 , could promote autophagy and delay senescence in cultured IMR-90 cells, while overexpression of the Drosophila homolog of WIPI1 , Atg18a , extended the life span in transgenic flies. Interestingly, the enhanced autophagy-lysosomal activity could be partially passed on to their offspring, as manifested by their higher levels of both autophagy-encoding genes and serum beclin 1 (BECN1). In light of the normal age-related decline of autophagy-lysosomal functions, these findings provide a compelling explanation for achieving longevity in, at least, female CENs, given the gender bias in our collected samples, and suggest that the enhanced waste-cleaning activity via autophagy may serve as a conserved mechanism to prolong the life span from Drosophila to humans.